2021
DOI: 10.1111/dom.14594
|View full text |Cite
|
Sign up to set email alerts
|

Insulin induces a progressive increase in the resistance of subcutaneous tissue to fluid flow: Implications for insulin pump therapy

Abstract: Aim: To determine the effect of insulin on the resistance of subcutaneous tissue to the flow of infusion fluids.Materials and methods: Thirty subjects with type 1 diabetes wore two Accu-Chek Spirit Combo insulin pumps with Accu-Chek FlexLink infusion sets (Roche Diabetes Care, Mannheim, Germany) for 7 days. One pump was filled with insulin aspart (Novo Nordisk, Bagsvaerd, Denmark) and used for continuous subcutaneous insulin infusion (CSII). The other pump was filled with insulin diluting medium (IDM; Novo Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Furthermore, other studies provide evidence that the insulin molecule is responsible for the pro-inflammatory tissue response at infusion sites. A recent study demonstrated that prolonged use of IIS over 3 days was associated with an increased tissue-related flow resistance (TFR) . This increase in TFR was attributed to the accumulation of macrophages and fibroblasts at the infusion site, as well as the deposition of collagen fibrils in response to the infused insulin .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, other studies provide evidence that the insulin molecule is responsible for the pro-inflammatory tissue response at infusion sites. A recent study demonstrated that prolonged use of IIS over 3 days was associated with an increased tissue-related flow resistance (TFR) . This increase in TFR was attributed to the accumulation of macrophages and fibroblasts at the infusion site, as well as the deposition of collagen fibrils in response to the infused insulin .…”
Section: Resultsmentioning
confidence: 99%
“…A recent study demonstrated that prolonged use of IIS over 3 days was associated with an increased tissue-related flow resistance (TFR) . This increase in TFR was attributed to the accumulation of macrophages and fibroblasts at the infusion site, as well as the deposition of collagen fibrils in response to the infused insulin . Additionally, the infusion of insulin via an insulin pump in diabetic swine was shown to impede insulin diffusion at the infusion site after 3 days of infusion, while infusion on the insulin buffer alone (without insulin) had no effect …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations